PENGARUH PERILAKU KERJA DAN KOMITMEN TERHADAP KINERJA SEKRETARIAT DINAS KOMUNIKASI DAN INFORMASI DAERAH ISTIMEWA YOGYAKARTA - Subiyantoro, Ary; Prihartanto Eko Wibowo; Khoiri Najib; Nur Azizah SW (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
This research aims to find out how work behavior and commitment influence employee performance in the Performance sector of the Secretariat of the Yogyakarta Special Region Communication and Information Service. This research uses a quantitative method with a sample size of 25 samples. The sampling method uses non-probability sampling with the researcher's technique using saturated sampling. Data analysis techniques use validity tests, reliability tests, multiple regression analysis, f tests and t tests. Based on the research results, the multiple regression equation Y = .300 + 0.527 X1 + 0.247 0.007 is smaller than 0.05 (0.007 < 0.05), f-count test results > f-table (39.961 > 3.342), sign value. 0.000 is smaller than 0.05 (0.000 < 0.05), this shows that the variable factors of work behavior and commitment influence the performance of the secretariat. The coefficient of determination test shows that the R Square is 0.747, meaning that the influence of work behavior and commitment variables on the performance of the Secretariat of the Yogyakarta Special Region Communication and Information Service is 74.7%, while the remaining 25.3% must be explained by other causal factors. originating from outside this regression method.